2005
DOI: 10.1111/j.1462-2920.2005.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of nutrient‐replete Microcystis PCC 7806 cultures is inhibited by an extracellular signal produced by chlorotic cultures

Abstract: The frequency of cyanobacterial blooms has been increasing all over the world. These blooms are often toxic and have become a serious health problem. The aim of this work was to search for population density control mechanisms that could inhibit the proliferation of the toxic bloom-forming genus Microcystis. Microcystis PCC 7806 cultured for long periods in liquid ASM-1 medium loses its characteristic green colour. When a medium of chlorotic cultures is added to a nutrient-replete culture, cell density increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Presently, we can only speculate on the function of these proteases as solubilizers of some exo-or endogenous protein complexes. In a recent report, it has been shown that prolonged starvation leads to proteolysis of phycobiliproteins in M. aeruginosa PCC7806, and that such chlorotic cells can survive stressed conditions (Dagnino et al 2006). A unique class of phycocyanin hydrolyzing enzymes with practically no similarity to any known proteases is responsible for degradation of cyanophycin (Richter et al 1999;Nanni et al 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Presently, we can only speculate on the function of these proteases as solubilizers of some exo-or endogenous protein complexes. In a recent report, it has been shown that prolonged starvation leads to proteolysis of phycobiliproteins in M. aeruginosa PCC7806, and that such chlorotic cells can survive stressed conditions (Dagnino et al 2006). A unique class of phycocyanin hydrolyzing enzymes with practically no similarity to any known proteases is responsible for degradation of cyanophycin (Richter et al 1999;Nanni et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…In bacteria, interaction between proteases and protease inhibitors could be a mechanism for protein stability and regulation which could have beneficial as well as deleterious effects on the producing organism (Schwarz and Zverlov 2006), and this attribute may also hold true for cyanobacteria. It has been shown that chlorotic cells of M. aeruginosa PCC7806 produce compounds with characteristic similarities to peptides, suppressing growth of the same species (Dagnino et al 2006). Correspondingly, it would be interesting to test whether the Microcystis strains that contain anabaenopeptins have carboxypeptidases and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…One and a half mL of chlorotic cultures were centrifuged for 20 s at 10000 rpm, the culture medium was removed, the pellet was resuspended in 1.5 mL of ASM-1 and the culture transferred to glass test tubes. These cultures were kept under white fluorescent light (16 h photoperiod) on shelves and their regreening observed periodically by regeneration experiments [ 20 ] or by flow cytometry monitoring red autofluorescence (FL4 photomultiplier) emission on a FACS Calibur (BD Bioscience). The experiments were carried out using four independent cultures, examined in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies we demonstrated that Microcystis cultures become chlorotic when maintained under nutrient limitation. The cells in these cultures seem whole and the cultures reacquire their characteristic blue green colour when returned to nutrient replete conditions [ 20 ]. It was also demonstrated that culture medium of chlorotic cultures induced chlorosis in green nutrient replete cultures.…”
Section: Introductionmentioning
confidence: 99%
“…These sometimes stochastic processes subsequently produce subpopulations that are very different to the population average. Recent evidence has revealed that these physiological subpopulations respond differently to environmental conditions and can produce signal compounds or inhibitors that dramatically affect and influence the overall population 3,4 .…”
Section: Introductionmentioning
confidence: 99%